PENGARUH KEBISINGAN BANDAR UDARA TERHADAP NILAI RUMAH Studi Kasus Bandar Udara Adi Sutjipto Yogyakarta - Budi Asmarawati; Eduardus Tandelilin (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2012)
Airport is one of the most important transportation facilities to increase the economy and development, however the negative impact of aircrafts operation is noise. Noise is an unwanted sound from certain activities on certain time which could disturb human health and unconvenience environment. The objective of this research is to analyze the noise of aircraft to residential value surrounding Adi Sutjipto Airport Yogyakarta. Based on economical criteria, statistical criteria and econometrical criteria shows there are five independent variables which influence significantly toward residential value. Variable building’s width, land’s width, distance to airport, and dummy variable building’s structure influence significantly positive to residential value. Toward residential value, distance to CBD influences significantly negative. Airport noise has negative effect toward residential value but not significant.Keywords: aircarft noise, human health, unconvenience environment, residential value